Dermolipoma e prolapso de gordura orbital - Duas entidades distintas - Ferraz, Lucieni Cristina Barbarini [UNESP]; Schellini, Silvana Artioli [UNESP]; Wludarski, Sheila Cristina Lordelo [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Moraes-Silva, Maria Rosa Bet [UNESP] (My University, 2002)
Purpose: To describe the clinical features of patients with dermolipoma and orbital fat prolapse. Methods: A retrospective 12-years survey was done concerning patients with dermolipoma and orbital fat prolapse, at the Faculdade de Medicina de Botucatu - UNESP. Results: During that time we found 20 patients with dermolipoma and 10 with orbital fat prolapse. Dermolipoma occurred mainly in children, more in female, and was frequently located at the external canthus, 7 patients had other ocular associated diseases. The orbital fat prolapse occurred also in Caucasians, more in males, the elderly, and in all but one occurred temporally. Conclusion: Dermolipoma and orbital fat prolapse have similar clinical appearances, but they are clearly distinct. Dermolipoma affects children, female, and orbital fat prolapse, elderly and males.
Dermolipoma and orbital fat prolapse - Two distinct entities
Keywords: Adipose tissue; Choristoma/diagnosis; Differential diagnosis; Lipoma; Orbital disease/diagnosis; Prolapse; Retrospective studies.